Introduction to the special issue on the intersection of professional selling and service. Issue 1 (2nd January 2017) - Rapp, Adam; Baker, Thomas L.
Abstract : As organizational operations continue to evolve in response to increasing customer demands, frontline research has begun to consider how traditionally separate organizational functions may be complementary to firm performance. Specifically, as sales and service activities become increasingly intertwined within the frontline role, this special issue explores how the sales and service functions interact within an organization. The articles contained in this special issue consider the interaction of sales and service with respect to customer, employee, and firm outcomes. After introducing evolving thought in the area, we provide an overview of five articles that make up this special issue. We conclude by offering additional areas of research.